Review Artikel: Aktivitas Antioksidan Ekstrak Amla (Phyllanthus emblica / Emblica officinalis) - Asih, Diah Jenari; Ni Kadek Warditiani; I Gede Sandi Wiarsana (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The production of free radicals that exceeds the need will cause various degenerative diseases. Therefore, to protect itself from free radicals, the body produces anti-free radical compounds or so-called antioxidants. Antioxidants are compounds that are able to inhibit damage caused by free radical oxidation. Natural antioxidant compounds may be sourced from several plants, one of which is the Amla plant (Phyllanthus emblica L.). The antioxidant activity of Amla extract is due to the presence of phenolic compounds such as gallic acid and flavonoids as well as the content of ascorbic acid. This is because these three compounds contain hydroxyl groups that can donate hydrogen atoms to free radical compounds and stabilize reactive oxygen species (ROS). The purpose of writing this review article was to determine the potential of Amla (Kemloko) as an antioxidant. The method used in this article review was a literature study related to the benefits of Amla extract as an antioxidant through a literature search process using research articles from the last 10 years. Based on the conducted research, it shows that Amla extract has the potential as a natural antioxidant.